Jamnalal Bajaj - Visual History of Business and Trade in India (2022)
Termed the 'Merchant Prince' by Mahatma Gandhi, Jamnalal Bajaj was an ardent patriot and a budding entrepreneur, who contributed both to the freedom movement and industrial development of India. Born to a Marwari family in Rajasthan in 1889, he was adopted by a business family in Wardha, and inherited the responsibilities and the reins of the family business at the age of 17, transforming it into one of the largest conglomerates of India, known as the 'Bajaj Group'. He was a staunch follower of the principles of Mahatma Gandhi and was an active part of the freedom struggle movements like the Non-Cooperation Movement (1920-22), Nagpur Jhanda (Flag) Satyagraha (1923), Boycott of Simon Commission (1928), Dandi March (1930), among other events. As a social reformer, he opened the doors of his family-owned temple to the Harijans (untouchables) and also established Mahila Ashram at Wardha & Mahila Shiksha Sadan in Ajmer encouraging women empowerment. Many institutions were set up in the legacy of Jamnalal Bajaj, including the prestigious Jamnalal Bajaj Institute of Management Studies.